INTERAKSI SIMBOLIK THE JAKMANIA PETUKANGAN DALAM MEMAKNAI KEHADIRANNYA DITENGAH MASYARAKAT - Nur Adli, Fathan; Syukron Anshori, Muhammad (Jurnal TAMBORA, 2021)
This study aims to explain how the symbolic interaction of football supporters of The Jakmania Petukangan in interpreting their presence in society. This study used descriptive qualitative method. Data collection techniques used by researchers are in-depth interviews and documentation. To analyze the data, the researcher used the symbolic interaction theory proposed by George Herbert Mead. The results of this study indicate that The Jakmania supporter group interprets its presence in the community, The Jakmania soccer supporters through the interactions made by the members of the group. The interaction carried out by the members of The Jakmania soccer fans group is through the elements contained in the activities organized by the members of the group. These elements include actions, gestures, costumes, The Jakmania.. In addition, there is a shift in the opinion of the Petukangan community regarding football supporters who were previously seen as often carrying out anarchic actions, now becoming a group whose presence provides benefits and positive impacts for the community. This is the first step so that the values ??contained in the activities of The Jakmania football supporters group in Petukangan can be interpreted and accepted by the Petukangan community in social life.